Mongolia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper and Statistical Appendix presents an overview of the fiscal developments in Mongolia since the late 1990s. It assesses the 'quality' of the ongoing fiscal adjustment. The paper examines the dramatic expansion of bank credit to the private sector over the last five years, asking what its sources are and what its consequences may be, particularly for the maintenance of macroeconomic and financial stability. The paper also describes recent developments in the garment sector in Mongolia.